PELATIHAN MENDELEY DESKTOP UNTUK PENULISAN KARYA TULIS ILMIAH BAGI GURU-GURU SMP NEGERI WINI - Justin Eduardo Simarmata; Ni Putu Yuni Astriani Dewi; Vinsensia Ulia Rita Sila; Muhammad Amran Shidik; Yunawati Sele (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aims to train skills and improve bibliography writing skills using the Mendeley Desktop in writing scientific papers for Wini State Junior High School teachers. Community service activity was carried out at Wini State Junior High School, North Central Timor Regency, East Nusa Tenggara. The training method is carried out in the following stages: lectures, demonstrations, discussions/questions and answers. The training activities were carried out face-to-face with the training participants as many as 13 Wini State Junior High School teachers. Based on the results of the training activities, it was found that the training of usingÂ  Mendeley Desktop has a positive impact toward development of teachers' abilities in writing scientific papers. The results of training activities related to the understanding of teachers in the technical use of Mendeley Desktop, a significant increase was obtained. Prior to the training, 8% of the training participants had a good understanding, 15% had sufficient understanding, and 77% had a poor understanding of using Mendeley Desktop in writing scientific papers. After the training, 62% of the participants had a very good understanding. 23% of participants have good understanding, the other 15% of participants have sufficient understanding. Thus, it can be concluded that the Mendeley Desktop application training was successful in carrying out knowledge transfer to the trainees.